Ethical Striving with Other-Than-Humans in Contemporary Improvised Music - Caroline Gatt (Suomen Antropologi)
This article presents an ethnographic analysis of the care and attention between other-than humans and musicians in the contemporary improvised music scene. From dominant Western perspectives, ethical relations are considered in anthropocentric terms: only persons with the capacity for self-awareness, autonomy, and rational judgment are considered able to engage in ethical practice. Even though there are increasing instances in Western contexts of attempts to expand definitions of personhood to other-than-humans, these retain an anthropocentric core. The improvising musicians with whom I worked question such a hegemonic narrative, and, coming from the understanding that the music they make emerges from a dense web of interconnected agencies, make music together with other-than humans. In other words, these musicians strive to relate with other-than-humans in mutual ethical relations of care. Second, even though the trope of improvisation features prominently in the philosophy of ethics, and even though ethical striving in recent anthropological studies of ethics has all the characteristics of improvisation, there is a surprising absence of discussion about improvisation itself. This article begins to address this gap by attending to the practices of skilled improvisers, and offers insights into how people ethically negotiate as yet unknown situations to them, in this case how to relate with other-than-humans. The focus on improvisation itself shows how ethical striving can be generative of ethical possibilities in intercultural and changing circumstances.